Evaluation of the histopathological spectrum of skin biopsies in patients with chronic kidney disease: A single-center experience - Amany A Fathaddin (Indian Journal of Pathology and Microbiology)
Background and Aim: Patients with chronic kidney disease (CKD), particularly those with end-stage renal disease (ESRD), frequently experience skin problems. Here, we present and discuss the histopathology results of skin biopsies performed on renal patients at our facility. Materials and Methods: We retrospectively reviewed all histopathological reports and slides of skin biopsies taken from CKD patients for the last 5 years at the Pathology Department of King Saud University Medical City, King Saud University in Riyadh. Design: This is a retrospective cross-sectional study. Results: Patients were 19 (43.2%) males and 25 (56.8%) females, with a mean age of 53.4 19.8 years. Diabetic nephropathy, hypertensive nephropathy, and lupus nephritis were the three most common kidney pathologies (59.1%, 11.4%, and 11.4%, respectively). Seventeen patients (38.5%) were receiving hemodialysis. Acquired perforating collagenosis (APC), which was observed in 16 (36.4%) of our patients, was the most prevalent skin pathology, followed by bullous drug reactions in nine (20.5%), leukocytoclastic vasculitis (LCV) in eight (18.2%), calciphylaxis in six (13.6%), and prurigo nodularis in five (11.4%) patients. Erythematous plaques and papules were the most prevalent skin conditions at the time of presentation in 12 patients (27.3%), followed by pruritus in six (13.6%) and ulcerations in six (13.6%) patients. Collected data were analyzed using the Statistical Package for Social Sciences (SPSS) version 26.0. Conclusion: A spectrum of skin conditions may be seen in CKD patients. The quality of life of CKD patients will be significantly improved by identifying and managing these conditions. Pathologists’ familiarity with this spectrum is important, as a correct histopathologic diagnosis will lead to a better outcome.